IBI379, a novel B cell maturation antigen/CD3 bispecific T-cell engager, displays high antitumor efficacy in preclinical models of multiple myeloma. (28th June 2022) - Fei, Keke; Ni, Haiqing; Zhu, Mengjia; Kuang, Zhihui; Wu, Min; Wu, Zhihai; Wang, Feifei; Zhou, Shuaixiang; Jing, Hua; Wu, Weiwei; Wu, Dongdong; Bai, Dongmei; et al.
Abstract: Multiple myeloma (MM) is a hematological malignancy that results from the malignant proliferation of plasma cells in the bone marrow. B cell maturation antigen (BCMA) is highly selectively expressed in malignant plasma cells and is a novel therapeutic target for MM. Here, we developed a bispecific T cell engager, IBI379, that targets BCMA and CD3, and investigated its antitumor efficacy against MM. IBI379 showed strong binding affinity with both BCMA and CD3, which triggered T cell activation, proliferation, and cytokine release. An in vitro study demonstrated that IBI379 induced the lysis of MM cells expressing differing levels of BCMA on the cell surface. Administration of IBI379 in H929 or Daudi-BCMA cell xenograft mouse models significantly inhibited tumor growth without inducing body weight loss. The mechanism of action study revealed the accumulation of CD4 + CD8 + T cells and granzyme B-positive T cells in tumors that were treated with IBI379. Moreover, administration of low dose of IBI379 in cynomolgus monkeys was well-tolerated and induced the depletion of BCMA + B cells and a mild transient increase of cytokines. Collectively, these results demonstrate that IBI379 is a highly potent therapeutic strategy for depleting BCMA-positive B cells and is a promising approach for the treatment of MM. Highlights: IBI379 triggered T cell activation, proliferation, and cytokine release. IBI379 induced the lysis of MM cells. Administration of IBI379 significantly inhibited tumor growth and triggered the tumor infiltration of CD4 + /CD8 + T cells. Administration of low doses of IBI379 in cynomolgus monkeys was well-tolerated and induced BCMA + B cell depletion.